The Influence of Physical Mixing and Impregnation on the Physicochemical Properties of Pine Wood Activated Carbon Produced by One-Step ZnCl2 Activation - Josphat Phiri; Hamidreza Ahadian; Maria Sandberg; Karin Granström; Thad Maloney (Micromachines, 2023)
In this study, two different sample preparation methods to synthesize activated carbon from pine wood were compared. The pine wood activated carbon was prepared by mixing ZnCl2 by physical mixing, i.e., “dry mixing” and impregnation, i.e., “wet mixing” before high temperature carbonization. The influence of these methods on the physicochemical properties of activated carbons was examined. The activated carbon was analyzed using nitrogen sorption (surface area, pore volume and pore size distribution), XPS, density, Raman spectroscopy, and electrochemistry. Physical mixing led to a slightly higher density carbon (1.83 g/cm3) than wet impregnation (1.78 g/cm3). Raman spectroscopy analysis also showed that impregnation led to activated carbon with a much higher degree of defects than physical mixing, i.e., ID/IG = 0.86 and 0.89, respectively. The wet impregnated samples also had better overall textural properties. For example, for samples activated with 1:1 ratio, the total pore volume was 0.664 vs. 0.637 cm3/g and the surface area was 1191 vs. 1263 m2/g for dry and wet mixed samples, respectively. In the electrochemical application, specifically in supercapacitors, impregnated samples showed a much better capacitance at low current densities, i.e., 247 vs. 146 F/g at the current density of 0.1 A/g. However, the physically mixed samples were more stable after 5000 cycles: 97.8% versus 94.4% capacitance retention for the wet impregnated samples.